The genetic communication and interaction between chronic kidney diseases and frailty - Xiaojun Wang; Xuchao Gu; Yuxin Zhang; Zhijun Bao (Clinical and Translational Discovery, 2023)
Abstract The prevalence of chronic kidney disease (CKD) is increasing due to the global ageing trend. Despite significant advancements in understanding the mechanisms of CKD, little research has focused on the prevention and treatment of associated complications such as frailty. In this review, we provide a summary of the current Genome‐Wide Association Studies (GWAS) of kidney diseases based on the unique genetic characteristics of kidneys and a review of the impact of metabolites associated with inflammageing on frailty and CKD. Additionally, the role of circadian rhythm in the intrinsic relationship between kidney and skeletal muscle has also been explored. This article offers insights into the potential communications and interactions between CKD and frailty to facilitate the current clinical treatments and improve the life quality for frail elderly individuals in coexistence of CKD.